2020
DOI: 10.1111/bjd.19040
|View full text |Cite
|
Sign up to set email alerts
|

Frontal fibrosing alopecia shows robust T helper 1 and Janus kinase 3 skewing

Abstract: Summary Background Frontal fibrosing alopecia (FFA) is a scarring alopecia with unclear pathogenesis and a progressive course. The disease has a major impact on patients’ quality of life and there is a lack of effective treatment to halt disease progression. Methods We profiled lesional and nonlesional scalp biopsies collected in 2017 from patients with FFA (n = 12) compared with scalp biopsies from patients with alopecia areata (AA) (n = 8) and controls (n = 8) to evaluate gene and protein expression, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 71 publications
(99 reference statements)
1
33
0
Order By: Relevance
“…Further reinforcing the concept of immune dysregulation in driving fibrotic processes in keloids is the increased T-cell expression, including Th2-related markers, in several fibrotic conditions, such as frontal fibrosing alopecia and scleroderma (65,66). In vitro studies have also demonstrated the profibrotic effects of the type 2 cytokines IL-4 and IL-13 (22), including increased collagen production in keloid fibroblasts after IL-13 stimulation (67).…”
Section: Discussionmentioning
confidence: 91%
“…Further reinforcing the concept of immune dysregulation in driving fibrotic processes in keloids is the increased T-cell expression, including Th2-related markers, in several fibrotic conditions, such as frontal fibrosing alopecia and scleroderma (65,66). In vitro studies have also demonstrated the profibrotic effects of the type 2 cytokines IL-4 and IL-13 (22), including increased collagen production in keloid fibroblasts after IL-13 stimulation (67).…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the composition of the inflammatory infiltrate in FFA, this is characterized by an increase in the percentage of CD8+ T cells [ 37 , 172 ], with a reversal of the typical CD4:CD8 ratio (which is approximately 2:1). However, this ratio is increased (>3:1) in uninvolved follicles in FFA, which may be because of the migration of CD8+ T cells from uninvolved areas to involved ones [ 170 ].…”
Section: Histopathologymentioning
confidence: 99%
“…Del Duca et al. recently determined that lesional skin from AA and FFA patients has significantly more CD8+ cytotoxic T cells, CD11c+ dendritic cells, and CD103+ CD69+ TRM cells when compared to nonlesional skin ( 87 ). In particular, FFA was shown to have a significant upregulation of the IFNγ/CXCL9/CXCL10 pathway and the JAK-STAT pathway ( 88 ), ( Figure 2D ).…”
Section: Trm In Alopecia Areata and Cicatricial Alopeciamentioning
confidence: 99%